A eletrocoagulação na terapêutica das lesões intra-epiteliais escamosas de alto grau do colo uterino - Lian, Ie Tjie [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
Analisar a eficácia da eletrocoagulação, como terapêutica nas pacientes portadoras de lesão intra-epitelial escamosa de alto grau de colo uterino. Pacientes e métodos: Estudaram-se prospectivamente 116 pacientes portadoras de lesão intra-epitelial escamosa de alto grau do colo de útero, distribuídas aleatoriamente, com 49 pacientes no grupo de estudo e 67 pacientes no grupo controle. Ambos os grupos foram avaliados quanto à idade, coitarca, paridade, hábito de tabagismo, número de parceiros sexuais, uso de drogas, presença ou antecedente de lesão condilomatosa vulvar, raça e escolaridade. Essas variáveis apresentaram-se homogêneas em ambos os grupos. Todas as pacientes do grupo de estudo e do grupo-controle foram submetidas a colposcopia...

Analyzing the efficiency of electrocoagulation as therapeutics in patients carrying high degree squamous intraepithelial lesion of the uterine cervix. Patients and methods: 116 patients carrying high risk intraepithelial lesion of the uterine cervix were prospectively studied, randomly distributed, being 49 patients in the study-group and 67 patients in the control-group. Both groups were evaluated according to age, first copulation, parity, smoking habits, number of sex partners, drug usage, presence or previous condylomatous lesion of the vulva, race and schooling. Such variables were found to be even in both groups. All patients from both groups were submitted to colposcopy, oncological cytology and biopsy of the uterine cervix. The study- group patients were treated with electrocoagulation of the uterine cervix and later submitted to conization after two months. The control-group patients underwent conization only. To assess the significance of the resuts, qui-square and Kappa agreement test were used. Results: In the study-group, electrocoagulation of the uterine cervix caused regression of the lesion in 73,5% of the cases, 20,4% remained unchanged, and there was progression... (Complete abstract click electronic access below)
Keywords: Colo uterino - Câncer - Tratamento; Cancer - Prevenção; Electrocoagulation; Dysplasia; Cervical pre-cancer